Efforts and Obstacles of the Banda Aceh Government in the Development of Child-Friendly City Policies - Nabila, Asyiatun; Rassanjani, Saddam; Afrijal, Afrijal (Buana Gender: Jurnal Studi Gender dan Anak, 2024)
The City of Banda Aceh, the capital of Aceh Province, has been committed to developing a Child-Friendly City Policy since 2013. However, to date, the City of Banda Aceh has still not achieved Child-Friendly City status, as evidenced by the absence of an increase in ranking in 2023 compared to the previous year. This city continued to maintain its Nindya level by the assessment in 2022. This research aims to identify efforts and inhibiting factors in developing Child-Friendly City policies, especially in the institutional cluster aspect. Using Institutional Development Theory by Milton J. Esman (1967), this research applies qualitative methods. Research findings show that Banda Aceh has not achieved Child-Friendly City status because the institutional indicators of a Child-Friendly City are not yet optimal, resulting in the fulfillment of children’s rights not being implemented comprehensively. The obstacles that cause Banda Aceh not to achieve this status involve limited budget resources, the absence of a Regional Action Plan, a lack of understanding of human resources regarding policies, minimal involvement from the business world, and the impact of the COVID-19 pandemic. Suggestions include: (i) Evaluate budget resource allocation for KLA, (ii) Immediately develop RAD-KAL as a guide for program implementation, (iii) Increase understanding of human resources through training, (iv) Encourage formal collaboration with the business world, (v) Designing an adaptive strategy for the disruptive impact of the pandemic for KLA. Keywords: Banda Aceh; Child- Friendly City; Public Policy.